Does it really get better with age? Life-cycle patterns of confidence in Germany - Markus Pannenberg; Tim Friehe (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper investigates if and how confidence at the individual level changes over the course of a life. We provide age profiles of a novel continuous confidence measure and the probability of overconfidence, conditioning on personality traits (including the Big Five and optimism), economic preferences, cognitive ability, and the individual's socioeconomic status. Our empirical work relies on a representative panel data set from Germany and individuals' self-assessment of their position in the gross wage distribution as our measure of confidence. We find that both the level of confidence and the overconfidence probability increase non-linearly with age up to the fifties. To illustrate the economic importance of the identified age gradient, we consider how both confidence measures predict savings and loan choices of households. We find that high wage-related confidence levels are, in all likelihood, a hindrance for prudent financial decisions in preparation for old age.
Keywords: D01; D91; J14; 330; Confidence; Age; Wage distribution; Germany; SOEP